2021
DOI: 10.1101/2021.05.28.446192
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Manganese transport by Streptococcus sanguinis in acidic conditions and its impact on growth in vitro and in vivo

Abstract: Streptococcus sanguinis is an oral commensal and an etiological agent of infective endocarditis. Previous studies have identified the SsaACB manganese transporter as essential for endocarditis virulence; however, the significance of SsaACB in the oral environment has never been examined. Here we report that a ΔssaACB mutant of strain SK36 exhibits reduced growth and manganese uptake under acidic conditions. Further studies revealed that these deficits resulted from the decreased activity of TmpA, shown in the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 87 publications
0
4
0
Order By: Relevance
“…If this is also true for SsaB, TmpA's function could become essential under the same condition. In our accompanying manuscript (Puccio et al., 2022), we found that loss of Δ ssaACB in SK36 was detrimental to growth in low‐pH media, which we hypothesize is due to acid sensitivity of TmpA. In VMC66, lack of Δ ssaACB had no effect in the same conditions, likely because MntH is still functional at the pH tested.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…If this is also true for SsaB, TmpA's function could become essential under the same condition. In our accompanying manuscript (Puccio et al., 2022), we found that loss of Δ ssaACB in SK36 was detrimental to growth in low‐pH media, which we hypothesize is due to acid sensitivity of TmpA. In VMC66, lack of Δ ssaACB had no effect in the same conditions, likely because MntH is still functional at the pH tested.…”
Section: Discussionmentioning
confidence: 68%
“…Likewise, we inserted the ssaACB genes into the site where tmpA had been. Based on the short distance separating tmpA and its upstream neighbors from one another and on the patterns of sequence read mapping to this region in our recent RNA‐seq studies (Puccio et al., 2022; Puccio et al., 2020), we believe the tmpA promoter lies upstream from SSA_1417 (SSA_RS06950). It is important to note, however, that by placing the ssaACB operon in the exact location of tmpA , we eliminated the need to identify the native tmpA promoter.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations